2015
DOI: 10.1115/1.4029455
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Boiling Critical Heat Flux of PF-5060 Dielectric Liquid on Microporous Copper Surfaces

Abstract: Pool boiling experiments are performed to investigate potential enhancement of critical heat flux (CHF) of PF-5060 dielectric liquid on microporous copper (MPC) surfaces and the effect of surface inclination angle. The morphology and microstructure of the MPC surfaces change with thickness. The experiments tested seven 10 Â 10 mm MPC surfaces with thicknesses from 80 to 230 lm at inclination angles of 0 deg (upward facing), 60 deg, 90 deg (vertical), 120 deg, 150 deg, 160 deg, 170 deg, and 180 deg (downward fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The increase in latent heat transfer mechanism (up to 10 times) was suggested as the main reason for the improved heat transfer recorded [10]. Similarly, El-Genk and Ali [11,12,13] employed the two-stage electrodeposition approach and produced microporous copper surfaces consisting of nanodendritic layers. Their experimental results showed that nucleate boiling heat transfer coefficient and CHF of 13.5 W/cm 2 K and 27.8 W/cm 2 could be achieved respectively with the microporous surface of 171 μm thickness [12].…”
Section: Direct Coatingmentioning
confidence: 97%
“…The increase in latent heat transfer mechanism (up to 10 times) was suggested as the main reason for the improved heat transfer recorded [10]. Similarly, El-Genk and Ali [11,12,13] employed the two-stage electrodeposition approach and produced microporous copper surfaces consisting of nanodendritic layers. Their experimental results showed that nucleate boiling heat transfer coefficient and CHF of 13.5 W/cm 2 K and 27.8 W/cm 2 could be achieved respectively with the microporous surface of 171 μm thickness [12].…”
Section: Direct Coatingmentioning
confidence: 97%
“…However, the CHF point must never be overcome because, in that case, the system is displaced to a film boiling regime. Some authors, such as El Genk and Ali [35], recommend maintaining the maximum heat flux below 70% of the CHF. The nucleate boiling heat flux in a pool boiling system can be estimated through the classical Rohsenow's correlation shown in Equation ( 5) [18].…”
Section: Working Fluidmentioning
confidence: 99%